Les Inventaires européens, un exemple : English Heritage (In Situ)
As part of the 'Maison du Moyen Age', an external department of the 'Bibliothèque nationale de France' based in Poitiers, which specializes in mediaeval civilization, the 'Service régional de l'Inventaire' in Poitou-Charentes is trying to collect the publications of other European institutions which publish material on aspects of heritage. English Heritage was the first to respond and to date the 'Service régional de l'Inventaire' has bought more than 200 books and CDs from it, whose series are presented below.